2010
DOI: 10.1177/1470595809359583
|View full text |Cite
|
Sign up to set email alerts
|

Home Versus Host — Identifying With Either, Both, or Neither?

Abstract: The present study examines the relationship between dual cultural identities and intercultural effectiveness. Upon the evidence of the regulating effects of cultural identities on individuals' cognitive, affective, and behavioral responses to cultural stimuli, we argue that cultural identities cast non-negligible influence on intercultural effectiveness. Focusing on the distinction between identity to one's cultural origin and identity to host culture, we hypothesize that individuals high on both identities ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Indeed effective boundary spanners may be able to switch between various cultural identities thus integrating knowledge from different cultural perspectives (Brannen and Thomas, 2010;Hong, 2010;Yagi and Kleinberg, 2011). In the international management and cultural studies literature, types of individuals termed biculturals (LaFromboise et al, 1993;Bell and Harrison, 1996) are becoming a recommended choice for global work arrangements as transnational intermediaries and knowledge mediators, with an emphasis on their boundary spanning capabilities (Brannen and Thomas, 2010;Johnson and Duxbury, 2010;Lee, 2010;Yagi and Kleinberg, 2011). Although there is as yet no evidence of a deliberate strategy for global organizations to recruit such individuals (Brannen and Thomas, 2010;Yagi and Kleinberg, 2011), they are more likely to attain management positions in global companies where cross-cultural communication is key (Bell and Harrison, 1996;Hong 2010;Friedman et al, 2012).…”
Section: Boundary Spanningmentioning
confidence: 99%
“…Indeed effective boundary spanners may be able to switch between various cultural identities thus integrating knowledge from different cultural perspectives (Brannen and Thomas, 2010;Hong, 2010;Yagi and Kleinberg, 2011). In the international management and cultural studies literature, types of individuals termed biculturals (LaFromboise et al, 1993;Bell and Harrison, 1996) are becoming a recommended choice for global work arrangements as transnational intermediaries and knowledge mediators, with an emphasis on their boundary spanning capabilities (Brannen and Thomas, 2010;Johnson and Duxbury, 2010;Lee, 2010;Yagi and Kleinberg, 2011). Although there is as yet no evidence of a deliberate strategy for global organizations to recruit such individuals (Brannen and Thomas, 2010;Yagi and Kleinberg, 2011), they are more likely to attain management positions in global companies where cross-cultural communication is key (Bell and Harrison, 1996;Hong 2010;Friedman et al, 2012).…”
Section: Boundary Spanningmentioning
confidence: 99%
“…Findings in cross-cultural contexts have consistently revealed that individuals with balanced identity configurations (both biculturals and marginals) are better able to adapt and flourish in host cultures than individuals with unbalanced identity configurations [20,23,63]. In this study we extend this reasoning by proposing that team leaders with balanced identity configurations (glocal or marginal) will be more effective in multicultural settings than leaders with one dominant identity (global or local) because they demonstrate higher levels of transformational leadership behaviors.…”
Section: Multicultural Team Leaders' Identity Balance and Leadership Effectivenessmentioning
confidence: 63%
“…Findings on adaptiveness and effectiveness in cross-cultural contexts show that bicultural individuals, who identify strongly with two national (local) cultures, tend to score higher in measures of creativity, effectiveness, cultural intelligence, and adjustment compared with those who identify disproportionately with either the home or host culture (i.e., who are separated or assimilated, respectively) [20,[61][62][63]. Unexpectedly, marginal individuals-whose identification with both the home and host cultures is equally low-also tend to score higher in creativity, effectiveness, cultural intelligence, and adjustment compared with assimilated or separated individuals, although not to the extent of biculturals [20,23,63]. This general pattern of findings poses a theoretical challenge to acculturation models that a priori separate the discussion of marginalization from the general discussion of balance, or that do not discuss marginalization at all [23,32,36].…”
Section: Identity Configurations Balance and Effectiveness In The Multicultural Environmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Biculturalism denotes identity structures where “people […] have internalized more than one cultural profile” (Brannen and Thomas, 2010, p. 6); see (Benet‐Martinez and Haritatos, 2005; Benet‐Martinez et al , 2002; LaFromboise et al , 1993; Lee, 2010; Molinsky, 2007; Ramirez‐Esparza et al , 2004; Sik and Lai, 2011; Sparrow, 2000; Tadmor and Tetlock, 2006). On the organizational level, “dual organizational identity” refers to a corresponding concept, indicating an individual's sense of identification with two organizational entities (Ashforth and Johnson, 2001; Chattopadhyay, 2005; Hernes, 1997; Pratt and Corley, 2007; Pratt and Foreman, 2000; Richter et al , 2006; Scott, 1997; Vora and Kostova, 2007; Vora et al , 2007).…”
Section: Images Of Dual Identity In International Business Researchmentioning
confidence: 99%